The Making of the Medieval Malay Hero Hang Tuah: Stories Behind the Epic Scene (Malay Literature, 2012)
The essay attempts to look at the scene behind the making of a hero in Malay medieval society. Such attempt is vital in order to understand not only the rise of a legendary hero, Hang Tuah, from his ordinary status in Sejarah Melayu (The Malay Annal) to his supra-human figure in the epic Hikayat Hang Tuah but also to gauge the social, political and psychological milieu behind the epic composition. The premise of the argument in this essay is that a hero is built and not born. Pushing it from there, the essay endeavours to prove the point by extensively reading on the milieu and time behind the emergence of Hikayat Hang Tuah. While exploring these, the essay also looks at the process of inventing the epic, which include identifying sources and materials borrowed, distorted, inverted and appropriated by the author to bring forth this traditional but unique literary creation.Keywords: epic, hero, heroism, heroic deeds, heroic age, ethnocentrism